Percutaneous Injection of Strontium Containing Hydroxyapatite versus Polymethacrylate Plus Short-Segment Pedicle Screw Fixation for Traumatic A2- and A3/AO-Type Fractures in Adults - Panagiotis Korovessis; Eva Mpountogianni; Vasileios Syrimpeis; Andreas Baikousis; Vasileios Tsekouras (Advances in Orthopedics)
Introduction. Polymethacrylate (PMMA) is commonly used in vertebroplasty and balloon kyphoplasty, but its use has been associated with complications. This study tests three hypotheses: (1) whether strontium hydroxyapatite (Sr-HA) is equivalent to PMMA for restoring thoracolumbar vertebral body fractures, (2) whether the incidence of PMMA leakage is similar to that of Sr-HA leakage, and (3) whether Sr-HAis is resorbed and substituted by new vertebral bone. Materials and Methods. Two age- and sex-matched groups received short percutaneous pedicle screw fixation plus PEEK implant (Kiva, VCF Treatment System, Benvenue Medical, Santa Clara, CA, USA) filled with either Sr-HA (Group A) or PMMA (Group B) after A2- and A3/AO-type thoracolumbar vertebral body fractures. The Visual Analog Scale (VAS) score and imaging parameters, which included segmental kyphosis angle (SKA), vertebral body height ratios (VBHr), spinal canal encroachment (SCE), bone cement leakage, and Sr-HA resorption, were compared between the two groups. Results. The average follow-up was 28 months. No differences in VAS scores between Groups A and B were observed at baseline. Baseline back pain in both groups improved significantly three months postoperatively. Anterior, middle, and posterior VBHr did not differ between the two groups at any time point. SKA was improved insignificantly in both groups. SCE decreased insignificantly in both groups on 12-month follow-up using computed tomography (CT). PMMA leakage was observed in one patient, while no Sr-HA paste leakages occurred. Sr-HA resorption and replacement with vertebral bone were observed, and no new fractures were observed. Conclusions. As all hypotheses were confirmed, the authors recommend the use of Sr-HA instead of PMMA in traumatic spine fractures, although more patients and longer follow-up will be needed to strengthen these results. This trial is registered with NCT03431519.